2006
DOI: 10.1016/j.ajog.2005.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of intake of folic acid–containing supplements among pregnant women

Abstract: Objective-This study describes the timing and correlates of folic acid supplement intake among pregnant women.Study design-Data from 2518 women with estimated delivery dates from 1997 to 2000, collected for the National Birth Defects Prevention Study, a population-based case-control study, were analyzed. Multinomial logistic regression was used to identify correlates of supplement intake.Results-Fifty-three percent of women began taking folic acid supplement during the periconceptional period, 35% during early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 22 publications
3
41
0
1
Order By: Relevance
“…21 In the national birth defects prevention study in the US women who did not take periconceptional folic acid supplements tended to be non-white, have lower education levels, be younger than 25 years old, be nulliparous, smoke, have no previous miscarriage and no fertility treatments, begin prenatal care and become aware of their pregnancy after the first trimester, have non-planned pregnancies, and eat less breakfast cereals. 22 Also other studies found that women who did not follow the supplementation recommendations were often under 25 or under 19 years of age, of low socio-economic status or born in another country. [23][24][25][26] However, it is important to note that in countries such as the US and the UK fewer than 50% of the pregnancies are planned, 27,28 which contrasts with countries such as Norway where 80% of the pregnancies are planned.…”
Section: Discussionmentioning
confidence: 99%
“…21 In the national birth defects prevention study in the US women who did not take periconceptional folic acid supplements tended to be non-white, have lower education levels, be younger than 25 years old, be nulliparous, smoke, have no previous miscarriage and no fertility treatments, begin prenatal care and become aware of their pregnancy after the first trimester, have non-planned pregnancies, and eat less breakfast cereals. 22 Also other studies found that women who did not follow the supplementation recommendations were often under 25 or under 19 years of age, of low socio-economic status or born in another country. [23][24][25][26] However, it is important to note that in countries such as the US and the UK fewer than 50% of the pregnancies are planned, 27,28 which contrasts with countries such as Norway where 80% of the pregnancies are planned.…”
Section: Discussionmentioning
confidence: 99%
“…The main comparable findings are summarised in Table 4 by country. The source papers were those listed in Table 1: Australia (71)(72)(73) ; Canada (74)(75)(76)(77)(78)(79)(80) ; Croatia (81) ; Denmark (82) ; Ireland (83)(84)(85) ; The Netherlands (67,86,87) ; New Zealand (88,89) ; Norway (90)(91)(92) ; Poland (93) ; Spain (94)(95)(96) ; the UK (NJ Wald, personal communication, 2005) (97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109)(110) ; and the USA (111)(112)(113)(114)(115)(116)…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…The impact of this factor increases with the proximity of the planned conception, with women who indicate their desire to become pregnant at some time in the future but with no specific plan, being no more likely to take a daily folic acid supplement than women never wanting to become pregnant (Cleves et al, 2004). The number of pregnancies was also found as a determinant of folic acid intake with women having had anterior pregnancies more likely to take folic acid supplements than women with their first pregnancy (Carmichael et al, 2006;Nasr Hage et al, 2011;Nilsen et al, 2006). Only one study conducted in Australia by Forster and his colleagues showed that having had other pregnancies is correlated with lower levels of folic acid intake (Forster et al, 2009).…”
Section: Determinants Of Folic Acid Intakementioning
confidence: 83%
“…Studies in the USA showed that African-American and Hispanic women were less likely to use folic acid supplements than Caucasian women (Ahluwalia et al, 2007;Carmichael et al, 2006;Cleves et al, 2004). Half of Hispanic women, and one third of African-American women aged 18-24 years, as compared to Caucasian women were taking folic acid supplements.…”
Section: Determinants Of Folic Acid Intakementioning
confidence: 99%
See 1 more Smart Citation